Algorithm for forming the structure of a selling website (by the example of developing landing page with high conversion for tourism business) - Ya. G. Usenko (Путеводитель предпринимателя)
The article is devoted to the compilation of the general structure of the selling site for the implementation of proposals for the expansion of a travel company using landing pages (landing pages). the main methods on which the authors of the study relied were: theoretical analysis and synthesis, content analysis, modeling and design methods, observation. The paper reflects the main theoretical features of building a landing page, substantiates the main properties of its Internet marketing tool, and the beneficial advantage of a landing page. It is emphasized that a high assessment of the structure of the landing is its structure, the effective organization of the processes of converting pages of visitors from its clients. Based on this case, the development and testing of the structure of the selling landing site is used, covering the broad elements included in the structure. As a result, the presented elements were integrated into the structure of the selling site aimed at the tourism business. Based on the results of model testing, a growth progress of 76% has been achieved.